Mental Health and Neurodivergence Disclosure Risk Mitigation in Private Higher Education Institutions: An Integrated Risk-Protection Framework to Support Sustainable Development Goals (SDGs) - Sharfika Raime; Norsafriman Abd. Rahman; Abdul Razak Yahaya; Syarizal Abdul Rahim; Fathilah Mohamed Aris (ASEAN Journal of Educational Research and Technology, 2027)
This study examines mental health and neurodivergence disclosure risk mitigation in private higher education institutions through an Integrated Risk-Protection Framework to support Sustainable Development Goals (SDGs). A quantitative cross-sectional survey was conducted involving 297 academic and non-academic staff from selected private higher education institutions in Selangor, Malaysia. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Structural power asymmetry, institutional trust deficit, stigma anticipation, and absence of safeguards reduce psychological safety in disclosure. Perceived enforceability of protection moderates these relationships and strengthens the explanatory power of the model. This study highlights perceived enforceability of protection as a key risk mitigation mechanism for developing inclusive, psychologically safe, and sustainable higher education governance.